Effect of presence of corpora lutea on cumulus expansion of in vitro matured bovine oocytes selected by trypan blue and brilliant cresyl blue tests - Carrera Chávez, José Maria (2018)
Trypan Blue (TB) and Brilliant Cresyl Blue (BCB) are used to select and determine viability and competence of oocytes, however, the effects of corpora lutea on cumulus expansion during in vitro maturation are still undetermined. Cumulus-oocytes complexes (COCs) from ovaries with ipsilateral (ICL), contralateral (CCL) and without corpora lutea in either ovary (OCL) were selected by visual examination, TB and BCB staining, and matured in vitro to evaluate cumulus expansion. The overall percentage of visually selected COCs was similar in ICL, CCL and OCL (P > 0.05). Proportions of live and mature COCs were similar in all groups (P > 0.05). The overall percentage of BCB+ COCs was 70.1%. BCB+ ICL COCs had less cumulus expansion (60.5%) than BCB+ CCL and OCL COCs (75.7 and 71.4%, respectively; P < 0.01). BCB− ICL COCs had less cumulus expansion (20.0%) than BCB− CCL and OCL (39.7 and 46.1%; P < 0.01). BCB+ CCL and OCL COCs showed the highest cumulus expansion index (P < 0.01). Presence of corpus luteum in the ovary affects negatively cumulus cells expansion. TB and BCB staining facilitate the selection of oocytes with higher degrees of cumulus expansion.